Choices, Caribbean agriculture, our way (CARAPN Port of SpainTT, 2012)
Relates the stories of several individuals, farm families and community groups in the Caribbean that have made the choice to enter, stay and focus on achieving success in agriculture.
Keywords: FOOD SECURITY